Pakistanâs Nuclear Policy & Development: A Sri Lankan Perspective - Aliff, S.M.; Fowsar, M.A.M (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
This paper aims to examine the historical background of Pakistanâs nuclear strategic doctrines in the context of nuclear deterrence policy of Pakistan. After years of research, Pakistan proudly set off an atomic bomb in 1998 and became the first Muslim nation to join the nuclear community. Primarily, the reason of nuclear deterrence of Pakistan will be propound as part of their historical conflicts with India and Indian threat was the major motive for Pakistan unveiling its nuclear card. The explosion caused tensions around the world and further strained diplomatic relations between Pakistan and its main rival India, which had detonated its own atomic device in 1974. The original Pakistani effort to build the atomic bomb began in the 1950s and reached a fever pitch during the Jimmy Carter administration when Pakistan made a deal with France for a reprocessing plant that could create fissionable plutonium. The other part would emphasize the key part of the nuclear programme of Pakistan. In such context, this paper is an attempt to touch various issues regarding development of nuclear power in Pakistan, while highlighting the role of external powers which would contribute to the transitory nature of their dynamic relations to develop nuclear power in Pakistan. The data were collected mainly fromÂ Â  secondary sources. The research concludes that the Pakistan may have no choice but to gain nuclear capability, to ensure its survival , and has developed its own nuclear weapons in order to strengthen its bargaining position vis-Ã -vis India and reduce its dependence on external sources.